Aftershocks of the 2012 Mw 7.6 Nicoya, Costa Rica, earthquake and mechanics of the plate interface - Chaves, Esteban (2017)
Subduction of the Cocos plate beneath the Nicoya Peninsula, Costa Rica, generates large underthrusting earthquakes with a recurrence interval of about 50 yrs. The most recent of these events occurred on 5 September 2012 (Mw 7.6). A vigorous sequence of more than 6400 aftershocks was recorded by a local seismic network within the first four months after the mainshock. We determine locations and focal mechanisms for as many aftershocks as possible with M ≥1:5 occurring within the first nine days of the mainshock, all aftershocks with M ≥3 through the end of 2012, and all events with M ≥4 through the end of 2015. We determine faulting geometries using regional full waveform moment tensor (MT) inversion for the largest events (M ≥4) and P-wave first-motion polarities for smaller events, producing a mechanism catalog with 347 earthquakes. Sixty percent of these events are identified as underthrusting, and their locations are compared with spatial distributions of mainshock slip, afterslip, prior interplate seismicity, and slow-slip phenomena to better understand the mechanical behavior of the plate interface. Most of the aftershocks on the megathrust occur up-dip of the coseismic slip, where afterslip is large, and between coseismic slip and shallow slow-slip patches. The pattern of interplate seismicity during the interseismic period is similar to that for the aftershocks but does not extend to as great a depth. The coseismic slip extends even deeper than the interplate aftershocks, suggesting that the mainshock ruptured a strongly locked patch driving down-dip slip into the conditionally stable part of the deep plate interface that also hosts slow slip. About 80% of the aftershocks have one nodal plane oriented favorably to promote failure from static stress changes following the mainshock and early afterslip, whereas most others occur in regions of large afterslip.